Responsiveness, Responsibility and Accountability in Clean Water Services at Regional Public Water Supply Utility Makassar City - Herlina Sakawati; Ahmira Ahmira; Widyawati Widyawati; sulmiah Sulmiah (Jurnal Office, 2022)
Clean water service is a type of service that is considered important because it relates to aspects of life, and this service was managed by Local Water Supply starting in the 90s, until 2019 in Makassar City it was managed by Regional Public Water Supply Utility after changing to the previous Local Water Supply structure. Problems in clean water services by Regional Public Water Supply Utility Makassar City continue to occur after these changes, so this research is directed to know responsiveness, responsibility, and accountability which are three important indicators in realizing quality clean water services. The qualitative research method was chosen by the author because it can make it easier to describe and express perceptions according to research data obtained from interviews, literature studies, and observations. The results of the study show that the lack of responsiveness by the Regional Public Water Supply Utility of Makassar City in clean water services is caused by the minimum number of employees. Responsibility by the Regional Public Water Supply Utility in providing services can be realized through the provision of communication facilities and easy service procedures, as well as responding to employee complaints. However, the inaccuracy of employees in carrying out their duties makes the accountability of clean water services have a bad assessment among the community.